Educating patients about health helps slow the progression of chronic kidney disease in the eastern region of India - Supriya Dasgupta; Reeti Debnath (MGM Journal of Medical Sciences)
Background: Chronic kidney disease (CKD) poses a well-documented burden, necessitating patient awareness of the importance of healthy lifestyle modifications to mitigate co-morbidities and mortality risks. Objective: This study aimed to assess the effectiveness of education-based conservative management in mitigating disease progression among CKD patients in the eastern region of India. Materials and Methods: A total of 248 CKD patients receiving outpatient department and inpatient department care at the nephrology and dialysis department of Belle Vue Clinic, Kolkata, West Bengal, India, were included in the study. Comprehensive data encompassing demographic details, socioeconomic status, clinical co-morbidities, and conservative management interventions via patient education were examined. The study compared the rise in creatinine levels with adherence to five key factors: dietary restrictions, medication compliance, follow-up appointments with physicians, management of co-morbidities, and adherence to lifestyle modifications. Each strategy was graded on a scale of 0, 1, or 2 based on compliance, with 0 indicating minimal or no compliance, 1 indicating moderate compliance, and 2 indicating strong compliance. Results: In this study, several factors were linked to elevated creatinine levels among CKD patients, including being in the middle-age range, male gender, living predominantly in urban areas, and working in business or service occupations. Additionally, a higher prevalence of co-existing conditions such as diabetes mellitus and hypertension was noted among CKD patients, along with documented instances of polycystic kidney disease, obstructive uropathy, and renal cell carcinoma. After educating CKD patients, those who scored 8–10 on compliance exhibited a decrease in creatinine elevation (0.35 mg/dL) among 120 cases from January 2022 to June 2023. Conversely, those with scores ranging from 5 to 7 (81 cases) showed moderate creatinine elevation (1.24 mg/dL), while those with scores of 0–4 (47 cases) demonstrated higher levels of creatinine elevation (5.48 mg/dL). Conclusion: This study concludes that the conservative management of CKD patients educates individuals about primary prevention of the disorder and provides a comprehensive understanding of secondary and tertiary prevention strategies. This cost-effective approach significantly impacts physical, mental, social, and psychological adjustment behaviors.